Existence and Uniqueness Results for Singular Boundary Value Problem of Weighted Generalized Fisher Type Differential Equation - Nadir Benkaci-Ali (Journal of the Indonesian Mathematical Society, 2021)
In this paper, we give existence and uniqueness results of nontrivial positive solution for the boundary value problem of the weighted and generalized Fisher's type differential equation.